Legal Protection for Muslim Consumers Regarding Halal Food Certification in Law Number 33 of 2014 (Gazetted) - Kurnia Pradana, Aditya Fajri; Muhammad Yunan Hidayat; Sugiyat, Sugiyat; Nafi' Hasbi, M. Zidny (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2024)
Purpose : “The purpose of this study is to analyse the legal protection for Muslim consumers of halal certified products in Law Number 33 of 2014. Method : This research uses a normative juridical approach, namely research that is focused on legal norms relating to legal protection for Muslim consumers against halal food certification in Law Number 33 of 2014. Result : The existence of various laws and regulations relating to halal labelling on food shows that the regulation is still partial. However, the existence of Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Guarantee provides more legal certainty. Business actors who are required to include halal labels on food are one of the moral responsibilities of business actors. Implication :The JPH Law provides several forms of legal protection for Muslim consumers. However, the implementation of the JPH Law still faces several obstacles. To improve legal protection for Muslim consumers, several efforts need to be made, such as increasing socialisation of the JPH Law, strengthening BPJPH, and improving coordination between institutions.